PEMANFAATAN TUMBUHAN OBAT OLEH MASYARAKAT SEKITAR HUTAN DI DESA PANGKALAN BUTON KABUPATEN KAYONG UTARA - Tantri, Susi (JURNAL HUTAN LESTARI, 2019)
The forest is one of the providers of biological natural resources that have great benefits for humans. Forests provide benefits in the form of wood forest products and non-wood forest products, one of the benefits of forest products felt by humans around the forest is medicines derived from plants. This study aims to obtain data on types of medicinal plants and how to process and use medicinal plants by the community in Pangkalan Buton Village Sukadana District, North Kayong Regency. The method used in this study is a survey method, with data collection using purposive sampling techniques with the help of interviews and questionnaires. Based on the results of research on the use of medicinal plants in Pangkalan Buton Village, Kayong Utara Regency, found 64 types of medicinal plants belonging to 41 families that can be used to treat 38 types of diseases. Based on habitus, it turns out the level of herbs is more widely used as a medicinal plant that is 23 types (35,94%). Based on the part that is used as medicine, the most widely used is the leaves which are 32 types (50%). Based on the method of processing, the most commonly used method by the community is by boiling as many as 37 types (57,81%). Based on the method of use, it turns out the way to drink is more widely used by the community as many as 43 types (67,18%).Keywords: Community, medicinal plants, part of plant, processing, traditional medicine,                    utilization